Pengaruh Media Pop Up Book Terhadap Hasil Belajar Ilmu Pengetahuan Alam dan Sosial (IPAS) Siswa Kelas V SD Negeri 88 Singkawang - Hengki; Mertika; Dewi Mariana (Institut Agama Islam Negeri (IAIN) Curup, 2024)
Learning success is supported by various components, one of which is the use of media. Learning media as a link of interaction in the learning process so that learning is effective for students. One of them uses Pop-Up Book media. The objectives of this study are: 1) to determine the difference in the learning outcomes of social studies students in grade V who use Pop Up Book media and classes that do not use Pop Up Book, 2) to measure the effect of the use of Pop Up Book Media on the learning outcomes of science science students in grade V of SD Negeri 88 Singkawang. A type of quantitative research with experimental methods. Research Design Nonequivalent Control Group Design. The research population of students of Grades VA and VB. The sampling technique uses Total Sampling. The Prerequisite Test uses the Saphiro Wilk Normality Test and the Homogeneity Test. Hypothesis testing, Independent Sample t-test and Effect Size Test. The results showed that 1) the average score of the posttest of the experimental class was 56.09 higher than the result of the control class which was 40.00. In addition, it can be seen that the output of the Independent sample t-test has an Equal Variances assumed significance value of 0.004 ˂0.05, it can be concluded that there is a difference in the learning outcomes of classes using Pop Up Books and classes not using Pop Up Books. 2) Pop Up Book has a high effect on the learning outcomes of science science students in grade V with the result of the Effect size = 0.94 which is in the High criterion.